Application of accelerated solvent extraction coupled with online two‐dimensional countercurrent chromatography for continuous extraction and separation of bioactive compounds from Citrus limon peel. Issue 19 (19th August 2020) - Li, Sainan; Liu, Chunming; Zhang, Yuchi; Shi, Dongfang; Tsao, Rong
Abstract: Drug discovery from complex mixtures, like Chinese herbs, is challenging and extensive false positives make it difficult to obtain compounds with anti‐Alzheimer's activity. In this study, a continuous method comprised of accelerated solvent extraction coupled with online two‐dimensional countercurrent chromatography was developed for the efficient, scaled‐up extraction and separation of six bioactive compounds from Citrus limon peels: neoeriocitrin, isonaringin, naringin, hesperidin, neohesperidin, and limonin. These active compounds were isolated and purified from the raw plant materials by two‐dimensional countercurrent chromatography separation via two sets of an n ‐hexane/ n ‐butanol/methanol/water solvent system: 0.23:1.00:0.25:1.13 and 0.47:1.00:0.38:1.46, v/v/v/v. The compounds were collected in yields of 0.22, 0.25, 0.10, 0.31, 0.29, and 0.28 mg/g, respectively, with purities of 95.79, 96.47, 97.69, 97.22, 98.11, and 98.82%, respectively. Subsequently, a simple and efficient in vitro method was developed for rapidly evaluating the acetylcholinesterase inhibitory activities of six bioactive components. Furthermore, the PC12 cell model and the in vitro metabolism of cytochromes P450 were employed to verify the monomers obtained from the continuous method. The results demonstrated that these six bioactive extracts from the C. limon peels were strong acetylcholinesterase inhibitors.